(untitled) (Experimental biology, 2009)
Accumulation of free proline in the germ of soft wheat under the influence of 0.01% CdCl2 solution and 2 % NaCl solution was investigated. It was confirmed that high content of free proline in the plant organism germs is the characteristics of tolerance to the action of abiotic factors. It was found that intensive accumulation of free proline is typical for salt-stable sorts like Nadezhda and Karashash, Shagala sort is more tolerant to the action of CdCl2.